PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU KEJAHATAN PROSTITUSI ANAK MELALUI TRANSAKSI ELEKTRONIK BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Kassandra Madya (Universitas 17 Agustus 1945 Samarinda, 2019)
Abstract Advances in technology and information have a positive influence on the development of social and economic activities in the world community. However, the development of technology and information not only has a positive influence, but also a negative influence. This negative influence can be seen along with the emergence of new criminal acts, namely cyber crime, which is in the form of prostitution carried out online. Regulations regarding the prohibition of online prostitution have been clearly formulated in positive Indonesian law, namely in the Criminal Code, Law Number 11 Year 2008 Regarding Information and Electronic Transactions, and Law Number 44 Year 2008 Concerning Pornography.But enforcement in this case is very difficult to do, because in online prostitution transactions that cross borders (bordeless)